ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2013-2015) - Putri Trianingrum, 13.05.52.0141; Wahyu Widati, Listyorini (Students' Journal of Accounting and Banking, 2017)
This study aims to examine the analysis of factors that affect the completeness of the disclosure of financial statements (Empirical Studies on Manufacturing Companies Listed on the Indonesia Stock Exchange in 2013-2015). The dependent variable in this study is the completeness of financial statement disclosure and the independent variables are profitability, liquidity leverage, public stock portion, firm age and firm size.The population in this study are all Manufacturing Companies located in Indonesia Stock Exchange in 2013-2015. A total of 269 samples were met as the sample of this study. This research uses purposive sampling method. The technique of testing the data by using multiple linear regression analysis. The result of the analysis shows that variables that have significant positive influence are profitability, and firm size is negative is leverage and age of company, non positive variable is not significant is public stock, and non negative variable is liquidity to disclosure of Financial Statement at Manufacturing company which is In Indonesia Stock Exchange 2013-2015.Keywords: Profitability, Liquidity, Leverage, Public Shares, Age of Company and Company Size To Disclosure